KEMAMPUAN MENENTUKAN POLA SPOK PADA KETERAMPILAN MEMBACA SISWA KELAS IV SD NEGERI SAWOJAJAR 02 - Khasanah, Maulidatun; Romli Triputra , Dedi; Mumpuni , Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe how the ability of grade IV students in understanding and determining SPOK patterns. The approach used is descriptive qualitative with data collection techniques through observation, interviews and documentation of teachers and grade IV students. In this study used triangulation to get the level of data absorption, the type of data analysis used in this study is triangulation. Based on the results of the study, it shows that the ability to determine spok patterns in the reading skills of fourth grade students of Sawojajar 02 State Elementary School, students already have a fairly good initial understanding of the basic elements of the sentence, especially the subject and predicate. However, most students still have difficulty in distinguishing objects and adverbs, especially in more complex sentences.